Proton Magnetic Resonance Studies of the Ferredoxins from Spinach and Parsley - Poe, M. (1971)
Contact-shifted resonances have been detected in the pmr spectra of both oxidized and reduced forms of spinach and parsley ferredoxins. These resonances are assigned to the β-CH(2) protons of four cysteine residues that are thought to bind the iron-sulfur redox center to the polypeptide chain. Temperature dependences of contact shifts reveal that the two iron atoms are antiferromagnetically coupled in both redox forms of each of these proteins. Thermal population of magnetic states gives rise to the contact shifts observed in the formally diamagnetic oxidized forms of these ferredoxins and accounts for the failure of contact shifts in the reduced forms exhibit to a Curie Law temperature dependence. It appears that the unpaired electron of reduced spinach and parsley ferredoxin is unequally distributed over the two iron centers. Valence states for the iron pairs of high-spin Fe(+3)-Fe(+3) and Fe(+2)-Fe(+3) for the oxidized and reduced forms, respectively, are compatible with the nmr results.